WILDLIFE SANCTUARIES IN THAILAND - Jintanugool, Jira (วารสารวนศาสตร์ไทย, 2022)
Under the WILD ANIMALS RESERVATION AND PROTECTION ACT B.E. 2503 currently recognized as WILDLIFE ACT, wildlife sanctuaries have been established in Thailand. With an exception of education and / or scientific research purposes; hunting, capture, and any kind of activity resulting to the disturbances of wild animals and wildlife habits in wildlife sanctuaries are prohibited by law. The first wildlife sanctuary was established in 1965 at Salak Phra, Kanchanaburi province. A number of 30 unique wildlife habitats has been declared as wildlife sanctuaries since 1965 covering the total areas of 22,192 sqkm. Their names, area coverage, habitat, and noteworthy species were described.